Chemical and thermal stabilization of CotA laccase via a novel one-step expression and immobilization in muNS-Mi nanospheres - Tomás Pose-Boirazian; Gemma Eibes; Natalia Barreiro-Piñeiro; Cristina Díaz-Jullien; Juan M. Lema; Jose Martínez-Costas (Scientific Reports, 2021)
Abstract A methodology that programs eukaryotic or bacterial cells to encapsulate proteins of any kind inside micro/nanospheres formed by muNS-Mi viral protein was developed in our laboratory. In the present study such “in cellulo” encapsulation technology is utilized for immobilizing a protein with an enzymatic activity of industrial interest, CotA laccase. The encapsulation facilitates its purification, resulting in a cost-effective, one-step way of producing immobilized enzymes for industrial use. In addition to the ability to be recycled without activity loss, the encapsulated protein showed an increased pH working range and high resistance to chemical inactivation. Also, its activity was almost unaffected after 30 min incubation at 90 °C and 15 min at the almost-boiling temperature of 95 °C. Furthermore, the encapsulated laccase was able to efficiently decolorate the recalcitrant dye RB19 at room temperature.